OKFŐ intézményi kontrolling módszertanának továbbfejlesztési kísérlete a kórházi gyakorlatban. - Kaszai Erzsébet (2021)
I prepared my diploma thesis at the Péterfy Hospital and Jenő Manninger National Insti-tute of Traumatology, where I work. My aim was to present the attempt to further develop the methodology of institu-tional controlling, and to describe the controlling system of our hospital and its operation through the analysis and comparison of the controlling results of 2019 and 2020. I raised a question about how a hospital controlling system can contribute to the operation of an in-stitution during normal, planned operation and during an unexpected event, a pandemic. My hypothesis is that hospital controlling processes are well regulated for normal, planned operation. After the introduction, I explained the relevance of the research and my objec-tives, and then I described the health care system together with the tasks of the Strategic Planning and Controlling Department of OKFŐ. In the next section, I presented the con-troller, the historical past of controlling, concepts, and the principles of controlling. A more detailed explanation was given in Section 4 on the operation of controlling, with the ap-proach to the development of unified controlling, the regulation of the chart of accounts and the function of the KKGIR system. Section 5 of my diploma thesis became key in demonstrating the operation of the class-controlling system. The controlling activity is con-tinuous. Its timeliness, however, is present in a special situation, caused by a pandemic, with extraordinary medical care tasks, organizational and economic expenditures, the rele-vance of which was not even conceivable at the beginning of the writing of the disserta-tion. I compared the results of controlling in the years 2019-2020 in a business economics approach. In several figures, I illustrate the results of 2020 by selecting specific groups - the in-patient care departments, and out-patient care units. In this section I present the hospital, its activities and its care responsibilities. Pride is the history of the hospital, which is connected to the Pest Merchants' Association from 1848. Finally, I summarized my dis-sertation, presented my suggestions, and concluded with a final thought. I have found that the hospital controlling system meets the textbook definition, but the practical application goes beyond that. The establishment of personal communication and joint coordination with the heads of the organizational units created a special practice in our institution. The hospital controlling system has already adapted to the normal operating order of the insti-tution, it works well by mapping the average, planned processes. The COVID-19 pandem-ic required ever-changing organizational transformations. The changes from time to time affected new organizational units, which required a great deal of flexibility from each hos-pital unit. In addition to the impact of the pandemic on the individual and on health, the economy and hospital management were also negatively affected. It had an extreme im-pact on revenue and expenditure. The health care system as a whole, alongside with the hospital system, was not prepared for the crisis.